Development stages of ESP in teaching English in Uzbekistan - Master’s student Karimova Nodira Bakhtiyor qizi (Zien Journals, 2024)
In this article, opinions are given about the implementation of ESP in Uzbekistan, its importance for representatives of various fields. Also, the work of the President of the Uzbekistan focusing on the development of foreign languages is briefly covered.
Keywords: ESP; languages; professional education; education